Parametric study of the composite spar lay-ups for the development of bend-twist coupled wind turbine blades structural and aerodynamic power performances - Razo, Christopher Isaac L.
Wind turbine blades (WTBs) are among the major components of the wind turbines. During operation, WTBs bend and twist due to the wind loads which can cause detrimental effects on its performance. This work aims to reduce the performance loss caused by the deformations by developing the bend-twist coupling capability of the blade, which can be achieved by using various multidirectional laminates for the spar cap of WTB. Two-way fluid-structure interaction (2-Way FSI) analysis is used in the present study, since the wind flow and pressure fields affect the structural deformations of the blade and the structural deformations affect the flow and pressure of the blade. In addition, a parametric study is conducted to investigate the effects of the fibre orientations and laminate lay-up of the spar on the bend-twist coupling and structural integrity of the blade. WTB with (-20)5:(20)5 spar cap laminates showed greatest potential in improving its power performance mostly under 20-25 m/s. It is more likely effective in off-shore application, where stronger winds are frequently present.